2002
DOI: 10.1021/je010183k
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Isotherms of VOCs onto an Activated Carbon Monolith:  Experimental Measurement and Correlation with Different Models

Abstract: A new material, activated carbon monolith, can be used as an adsorbent to remove volatile organic compounds (VOCs). Vapor-solid adsorption isotherms of three VOCs (toluene, 1-butanol, and ethyl acetate) on an activated carbon monolith were measured at: 20 °C, 60 °C, 100 °C, and 140 °C using a microbalance. The experimental data were correlated with the following adsorption isotherm models: Langmuir, Freundlich, Langmuir-Freundlich, and Toth equations. The Langmuir-Freundlich and Toth equations provided good fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 6 publications
1
41
0
Order By: Relevance
“…Bituminous coal is the most industrial grade carbon used for the air and water applications (Cooper and Alley, 1994). Activated carbon can be classified as powdered activated carbon (PAC), forms of activated carbon fibers (Bansal et al, 1988(Bansal et al, , 2005, activated carbon monoliths (Luo et al, 2002(Luo et al, , 2006, activated carbon fiber cloths Ramirez et al, 2004) and granular activated carbon (GAC).…”
Section: Adsorbentsmentioning
confidence: 99%
“…Bituminous coal is the most industrial grade carbon used for the air and water applications (Cooper and Alley, 1994). Activated carbon can be classified as powdered activated carbon (PAC), forms of activated carbon fibers (Bansal et al, 1988(Bansal et al, , 2005, activated carbon monoliths (Luo et al, 2002(Luo et al, , 2006, activated carbon fiber cloths Ramirez et al, 2004) and granular activated carbon (GAC).…”
Section: Adsorbentsmentioning
confidence: 99%
“…A number of studies have reported monolithic adsorbents for the removal of volatile organic compounds (VOCs) from air [23,[34][35][36][37][38]. Shah et al [39] studied the removal of volatile organic compounds (VOCs) from air using monoliths and performed simulations for comparing the performance of their novel adsorbents with a packed bed of pellets.…”
Section: Monolithic Adsorbentsmentioning
confidence: 99%
“…Yu et al [35] used activated carbon monoliths for VOCs removal using electrothermal desorption method. Yu et al [105,106] investigated the electrothermal swing adsorption (ESA) process with an activated carbon monolith (400 cpsi) as adsorbent for adsorption of toluene vapours.…”
Section: Use Of Adsorbent Structures In Electrical Swing Adsorption (mentioning
confidence: 99%
“…Parallel channel monolithic structures with controllable shape, cell density and wall thickness have been reported for their use in adsorptive gas separation systems (Kodama et al, 1993;Gadkaree, 1997;Li et al, 1998;Lee et al, 2000;Yu et al, 2002;Yates et al, 2003). The main advantage of such configurations resides in their low pressure drop and higher mass transfer rates.…”
Section: Introductionmentioning
confidence: 99%